Remittances and poverty alleviation - Bayes, Abdul; Hossain, Mahahbub; Rahman, ANM Mahfuzur (The Financial Express, 2016)
Abdul Bayes is Professor of Economics at Jahangirnagarr University, Mahabub Hossain is a Distinguished Professor, BRAC University and ANM Mahfuzur Rahman is from Data Management Unit BRAC.